Investigating the effects of multisensory illusions on pain and body perception - Themelis, Kristy (2017)
The amount of pain we feel is not always directly related to the amount of damage our body suffers. In fact, research over the last decade has shown that the experience of pain is strongly linked with how we feel about our body, including its shape and how much we like it. Chronic pain is associated with a distorted mental representation of the body, which can have a significant impact on everyday live. Evidence suggests that multisensory illusions can modulate pain and can lead to changes in body perception. However, the factors that may contribute to previously observed analgesic effects remain unclear. This thesis aimed to systematically asses the effects of these illusions on pain and body representation in both healthy individuals and individuals with chronic pain. First, this thesis aimed to investigate the effects of multisensory illusions on body representation, sense of body ownership, and pain in healthy individuals. Chapter 2 found that multisensory illusions can alter perceived body shape, body satisfaction, without losing ownership. Chapter 3 examined whether distorting the size and shape of the virtual hand could modulate pain in healthy participants. No evidence was found for this, which could indicate that pain is not necessarily affected by virtual body ownership over a distorted hand. Having established that multisensory illusions can alter body perception and the affective experience of the body, the second aim of this thesis was to investigate the effect of multisensory illusions on body representation, body ownership, and pain in individuals with hand osteoarthritis (HOA). Chapter 4 investigated whether people with HOA performed differently on a hand laterality motor task to investigate whether people with HOA present with a disruption of the working body schema. Though no evidence was found for a general impairment on this task, the findings suggested that performance on the task was mediated by the presence of pain. Chapter 5 investigated effects of multisensory illusions on pain and pain sensitivity in individuals with HOA. The results demonstrated that viewing the body could modulate pain; and affected body representation, body ownership, and agency. Chapter 6 examined the effects of multisensory illusions on subjective and objective aspects of body perception in people with HOA of the hands, compared to healthy controls. Though no evidence was found for an analgesic effect of the illusion, results showed that participants with HOA have a disturbed experience of the size of their hand compared to healthy controls. Furthermore, the results suggest that individuals with HOA may have an abnormally high body dissatisfaction that cannot readily be altered by multisensory illusions. This thesis found mixed support for the analgesic effects of multisensory illusions on pain in HOA and concludes that the specific context in which pain occurs is important. It also highlights the many perceptual and cognitive factors that may contribute to the modulation of pain. The findings imply that future work should focus on interventions that are more portable and accessible for home use, and focus on developing research around the effects of repeated and prolonged exposure to multisensory illusions on pain, body image disturbances and body dissatisfaction.